A new combination chaotic system and its application in a new Bit-level image encryption scheme. (February 2022) - Zhou, Wenjie; Wang, Xingyuan; Wang, Mingxu; Li, Dongyan
Abstract: In this paper, a new combination chaotic system (NCCS) is proposed for image encryption. The proposed system has larger key space and exhibits better cryptographic features in dynamics than their original one-dimensional chaotic map. Meanwhile, using NCCS, a new bit-level image encryption scheme is proposed. The core of the scheme includes the generation of the plaintext-related key streams by SHA-512 Hash function and random decimal points sequence, NCCS-based bit-level image confusion and diffusion operations. Experimental results and security analyses show the validity of the proposed algorithm in terms of high security, and demonstrate the good chaotic behavior of NCCS.